2013
DOI: 10.1080/19440049.2013.797114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Korean consumer exposure to sodium saccharin, aspartame and stevioside

Abstract: The dietary intakes of sodium saccharin, aspartame and stevioside were estimated on the basis of food consumption data of the Korean consumer and the concentration of sweeteners in processed foods. Results were compared with the acceptable daily intake (ADI) of sweeteners. Among the 28 food categories for which the application of sodium saccharin, aspartame and stevioside is permitted in Korea, they were detected in 5, 12 and 13 categories, respectively. The estimated daily intake (EDI) of sodium saccharin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 15 publications
4
22
0
Order By: Relevance
“…Similar results were reported in studies conducted in Korea, Australia and New Zealand and Brazil (50)(51)(52)60) . A review by Renwick (48) reported that the overall intakes of LCS had not increased significantly during the preceding decade, although it has been reported elsewhere that the numbers of people consuming LCS were increasing (69) .…”
Section: Actual Low-calorie Sweeteners Exposuresupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were reported in studies conducted in Korea, Australia and New Zealand and Brazil (50)(51)(52)60) . A review by Renwick (48) reported that the overall intakes of LCS had not increased significantly during the preceding decade, although it has been reported elsewhere that the numbers of people consuming LCS were increasing (69) .…”
Section: Actual Low-calorie Sweeteners Exposuresupporting
confidence: 90%
“…The optimal methodology for assessing habitual LCS exposure is a 1-2-week prospective, brand level diary, including information on portion sizes along with brand-specific information on LCS concentrations in products (48) . Given that obtaining such refined individual level data can be time and resource intensive for investigators, as well as labour intensive for participants, a variety of dietary assessment tools have been utilised in the past including 24-h recalls (49)(50)(51)(52)(53) , FFQ covering various durations (54)(55)(56)(57) and food diaries lasting 2 d (58) , 5 d (59) , 7 d and 14 d (60) . Some studies used a combination of retrospective and prospective intake data in order to first identify potential high consumers and then to further investigate these high consumers (61,62) .…”
Section: Methods Of Assessing Exposure To Low-calorie Sweetenersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucralose is the most frequently used ASW in the U.S.A. and is found in ∼1500 products as compared to acesulfame (1103 products) and aspartame (974 products); 30 however, aspartame is the most widely used ASW in processed foods at relatively higher concentrations (as much as 5602 mg/kg) in Korea. 31,32 Artificial Sweeteners in Suspended Particulate Matter. This is the first report of occurrence of ASWs in SPM; aspartame was found in 92% of influent SPM samples at a mean concentration of 444 ng/g dw, followed by acesulfame (92 ng/ g) and saccharin (49 ng/g).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In Asia, a total of 20 studies were identified, two of which were conducted in China [20,21], one among Indian individuals [22], eight conducted in Japan [23,24,25,26,27,28,29,30,31], and nine conducted for Korean population groups [32,33,34,35,36,37,38,39,40]. The main results and conclusions are presented in Table 1.…”
Section: Methodology and Trends In Intakementioning
confidence: 99%